Green Chemistry Approaches Using Microwave Irradiation: A Comprehensive Review (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Aim: This review aims to examine the role of green chemistry principles and microwave irradiation technique in enabling sustainable, eco-friendly chemical synthesis. Materials and Methods: The review compiles and analyses existing literature on green chemistry concepts, the twelve guiding principles established by Anastas and Warner, and the mechanism, applications, and comparative benefits of microwave-assisted synthesis over conventional heating methods. It draws on findings from published research studies, examining how this technique performs against traditional synthesis in terms of reaction speed, yield, purity, selectivity, energy efficiency, and solvent use, along with its applications in organic synthesis, nanotechnology, and pharmaceutical development, as well as its known limitations such as equipment accessibility, compound compatibility, and safety concerns. Conclusion: Microwave irradiation stands out as a valuable green chemistry tool, offering faster, cleaner, and more efficient synthesis compared to traditional techniques. Supported by the twelve principles of green chemistry, it minimizes waste and hazardous byproducts while improving reaction outcomes, indicating strong potential for continued development in sustainable chemical research.
Keywords: Green Chemistry; Microwave Irradiation; Microwave-Assisted Synthesis; Green Synthesis; Sustainable Chemistry; Organic Synthesis; Energy Efficiency; Nanotechnology